Carbonized Cotton Fabric for High‐Performance Wearable Strain Sensors. (2nd November 2016) - Zhang, Mingchao; Wang, Chunya; Wang, Huimin; Jian, Muqiang; Hao, Xiangyang; Zhang, Yingying
Abstract : Recent years have witnessed the booming development of flexible strain sensors. To date, it is still a great challenge to fabricate strain sensors with both large workable strain range and high sensitivity. Cotton is an abundant supplied natural material composed of cellulose fibers and has been widely used for textiles and clothing. In this work, the fabrication of highly sensitive wearable strain sensors based on commercial plain weave cotton fabric, which is the most popular fabric for clothes, is demonstrated through a low‐cost and scalable process. The strain sensors based on carbonized cotton fabric exhibit fascinating performance, including large workable strain range (>140%), superior sensitivity (gauge factor of 25 in strain of 0%–80% and that of 64 in strain of 80%–140%), inconspicuous drift, and long‐term stability, simultaneously offering advantages of low cost and simplicity in device fabrication and versatility in applications. Notably, the strain sensor can detect a subtle strain of as low as 0.02%. Based on its superior performance, its applications in monitoring both vigorous and subtle human motions are demonstrated, showing its tremendous potential for applications in wearable electronics and intelligent robots. Abstract : Based on carbonized plain weave cotton fabric, a wearable strain sensor with high sensitivity and large workable strain range (up to 140%) is fabricated through a cost‐effective, scalable, and green process. Its working mechanism is investigated and its application in detection of both subtle and large deformation of the human body is demonstrated, promising great potential in wearable electronics.